The Burden of Depressive Symptoms and Associated Factors in People Living with HIV/AIDS: A Global Systematic Review - Dr. Mohammad Ali K. Muqri; Dr. Abdullah Ahmad B. Alghamdi; Dr. Tahani Yahya Ali Madkahli; Amarlina Norain Binti Zulkifli; Ghadah Yahia Mathkoor; Rania Mohammed Ghaleb (Journal of Science in Medicine and Life, 2026)
Background: Among those living with HIV/AIDS (PLWHA), depression is a common and frequently under-addressed mental health illness that affects their quality of life, drug compliance, and general health outcomes. The worldwide burden of depressive symptoms among people living with HIV, nevertheless, varies greatly across many areas and demographic groups. This methodical review and meta-analysis tried to determine the prevalence of depression among people living with HIV and pinpoint variables influencing its variation across worldwide settings. Methodology: To find studies published between 2015 and 2025 that reported the prevalence of depressive symptoms in PLWHA. The meta-analysis comprised 38 studies including 144,603 PLWHA. With different cut-off points, the investigations used a number of depression evaluation tools, including CES-D, PHQ-9, BDI-II, and MINI-KID. The pooled prevalence of depression was determined, and subgroup analyses were conducted to investigate how socioeconomic characteristics, geographical areas, and assessment instruments affect depression prevalence. Results: Among PLWHA, the meta-analysis found a pooled prevalence of depression of 30% (95% CI: 25%–36%), with significant heterogeneity between studies (I² = 99.5%, P = 0). Studies using the CES-D instrument showed the highest incidence; BDI and MINI-KID scales reported lower rates. Though males had a little lower risk (RR = 0.89, 95% CI: 0.77-1.02), gender did not show a notable influence on depression risk. Living with a partner also reduced the risk of depression (RR = 0.70, 95% CI: 0.57–0.86). Conclusion: Among PLWHA, depression is a major worldwide health concern with differing prevalence rates across geographic areas and demographic groups. Higher rates of depression among vulnerable subgroups like pregnant women, adolescents, and the elderly emphasize the need of customized mental health interventions. The results emphasize the necessity of including mental health care into HIV care and tackling socio-cultural elements to lower PLWHA's mental health load.